Strategies and Policies for The Acceleration of Bali Tourism Recovery - Astawa, I Putu (E-Journal of Tourism; Volume 9 Number 1 (March 2022), 2022)
Bali tourism has been suspended due to the COVID-19 pandemic. Therefore, efforts to revive tourism and restore the economy in Bali are needed. The main objectives of this study are (1) to analyze the efforts to build the trust of the tourists to visit Bali, (2) to analyze the policies to encourage tourists to come to Bali. This study utilized a qualitative approach. The study was conducted in Bali, and data was collected through interview, observation, and documentation techniques. The key informants in this study were the Heads of the following institutions: Bali Provincial Tourism Office, Statistics of Bali Province, Bali Provincial Health Office, and Bank Indonesia. The result of this study revealed that building trust from the tourists to visit Bali can be done by suppressing and reducing the spread of COVID-19, repetition of public awareness socialization campaigns about health protocols implementation, providing healthcare facilities, medical personnel, and paramedics, tight travel control at Bali’s entry and exit points, vaccination of tourism workers and the community, and implementation of green zones. Furthermore, the strategies to encourage tourists to come to Bali are free covid corridor, meeting incentive conference exhibition, work from Bali, influencer collaboration through the “We Love Bali” program, and digitalization of inclusive tourism. This study is essential to be conducted to assist in restoring tourism and economic conditions in Bali. Keywords: Tourism, economy, trust, travel, tourists